Community User Groups : Vehicles for Collective Action - or Personal Gain? - Aslop, Ruth; Forusz, Samantha (World Bank, Washington, DC, 2012)
A study of three user groups in India suggests that such groups rarely perform as expected. The note is based on such study, which comprised the performance of 100 community user groups, involved in the collective management of natural resources in three Bank-supported projects in the country. Two aspects of performance were evaluated: groups achievement, and group functioning. Among the issues analyzed were member perceptions of group's achievement of formal, and member objectives, participation in different group activities, realization of benefits, group transparency, and, internal accountability. Despite the hierarchical, social context, distribution of benefits was not biased toward any social, or economic group. However, women played almost no role in group affairs - regardless of their caste or class. In all three cases, members knew very little about group governance, and, regardless of awareness, accountability mechanisms were rarely - if ever - applied. The note emphasizes that low transparency can destroy a group's ability to promote cooperation, and collective action, while project designers, and implementers need to better understand member objectives, be more pragmatic with expectations of local organizations, and functions, and, be more realistic about accomplishments given the resource management available vs. required.